2012
DOI: 10.1007/s00406-012-0315-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences between unipolar and bipolar I depression in the quantitative analysis of glutamic acid decarboxylase-immunoreactive neuropil

Abstract: Alterations in GABAergic neurotransmission are assumed to play a crucial role in the pathophysiology of mood disorders. Glutamic acid decarboxylase (GAD) is the key enzyme in GABA synthesis. This study aimed to differentiate between unipolar and bipolar I depression using quantitative evaluation of GAD-immunoreactive (GAD-ir) neuropil in several brain regions known to be involved in the pathophysiology of mood disorders. Immunohistochemical staining of GAD 65/67 was performed in the orbitofrontal, anterior cin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Postmortem interval, time of fixation, shrinkage, sex, age, and brain weight did not differ among the groups. Negative correlations between neuroleptic and/or lithium dose were reported in the medial temporal cortex and the OFC but not the DLPFC (Gos et al, 2012). These data were supported by a meta-analysis of Stanley Foundation Neuropathology Consortium samples (schizophrenia, BD, MDD, and controls, 15 per group) matched for age, gender, race, postmortem interval, mRNA quality, brain pH and hemisphere (Kim and Webster, 2010).…”
Section: The Orbitofrontal Cortex (Ofc)mentioning
confidence: 86%
See 1 more Smart Citation
“…Postmortem interval, time of fixation, shrinkage, sex, age, and brain weight did not differ among the groups. Negative correlations between neuroleptic and/or lithium dose were reported in the medial temporal cortex and the OFC but not the DLPFC (Gos et al, 2012). These data were supported by a meta-analysis of Stanley Foundation Neuropathology Consortium samples (schizophrenia, BD, MDD, and controls, 15 per group) matched for age, gender, race, postmortem interval, mRNA quality, brain pH and hemisphere (Kim and Webster, 2010).…”
Section: The Orbitofrontal Cortex (Ofc)mentioning
confidence: 86%
“…A recent immunohistochemistry study using a monoclonal antibody to both GAD 65 and GAD 67 reported a decrease in GADimmunoreactive neuropil in layers III and V of the left DLPFC in BD (n = 12) but not MDD (n = 9) subjects relative to controls (n = 18) (Gos et al, 2012). Duration of illness was greater in the BD group compared with the MDD group but did not correlate with GAD immunoreactivity in the DLPFC.…”
Section: The Orbitofrontal Cortex (Ofc)mentioning
confidence: 97%
“…In the PFC, the overall results have been equivocal, with one study finding increased density of GAD-immunoreactive (IR) cells, 35 another finding significant decreases, 36 and a third finding no change. 37 Additionally, an investigation of GAD enzymatic activity in the PFC of suicide patients compared to healthy controls found no changes in GAD function. 38 Similarly, results in the orbitofrontal cortex, temporal cortex, and thalamus up to this point have had mixed results.…”
Section: Evidence For Altered Gabaergic Neurotransmission In Mdd: a Cmentioning
confidence: 99%
“…In a metaanalysis, Kishi et al [5] are reporting two SNPs of the receptor gene to be associated with major depression and overlapping with bipolar disorder. Therefore, the neurobiological classification of subtypes of mood disorders is an unresolved challenge and alterations in GABA synthesis have been proposed to discriminate unipolar from bipolar I depression [6]. Discrimination of unipolar and bipolar depression at early stages of the illness could help improving specific treatment regimes.…”
mentioning
confidence: 99%